PENGEMBANGAN DESA WISATA CIKOLELET BERBASIS MASYARAKAT DI DESA CIKOLELET KECAMATAN CINANGKA KABUPATEN SERANG BANTEN - Bagus Saifullah Agung Gumelar (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2020)
Development of tourist villages as an effort to reduce poverty. This study amis, i.e: 1) To identify the process of developing Cikolelet Tourism Village, 2) to analyze are the benefits of Cikolelet Tourism Village for the community's economy? 3) to describe the supporting and inhibiting factors in community empowerment efforts through the development of Cikolelet Tourism Village. In this study using a qualitative descriptive method, because it wants to describe the object of research based on the facts that occur in the research place. For data collection techniques using observation, interviews, and documentation. The conclusion from the researcher is that the process of developing Cikolelet Tourism Village is carried out in collaboration with the Serang Regency Tourism Office, the Banten Province Tourism Office and the STP Trisakti College. From this process, there are benefits from the economic sector in tourism activities with a profit sharing system for LMDH/managers by 40%, Perhutani 40% and BUMDES 20%, while from the surrounding community they get income from the shop sector (UMKM). However, there is a need for supporting factors, namely assistants in facilitating training program activities that are very supportive of the development of Cikolelet Tourism Village, and the need for the government to improve accessibility to leading tourist attractions in Cikolelet Village. The inhibiting factor is the unavailability of clean water sources in some of the leading natural attractions in Cikolelet Village, such as Cibaja Peak and Pilar, so that the community still has to work together to bring clean water to meet the tourists' facilities.